Entomofauna of the National University of Colombia, Bogota campus: Descriptive parameters of its composition and abundance - Camero, Edgar; Murcia-Betancourt, Luis Miguel; Zúñiga-Totena, Miguel Antonio; García-Marín, Sofía (Revista Colombiana de Entomología, 2022)
The vertical composition of the entomofauna was analyzed in three areas of the Universidad Nacional de Colombia Bogotá campus, between 2018 and 2020 in order to make known especially to the general community, the faunal richness found in this relict of green areas within the urban landscape. To collect the specimens, stratified samplings were carried out in areas with different plant covers on the university campus. The collected entomofauna was determined at the family level and the values of Brillouin diversity (B), dominance (D) and Simpson’s fairness (1-D) were established. The efficiency of the samplings was evaluated by means of the Chao-1, abundance models of the sampling sites were established to know their relationship with the diversity values and the trophic level of each of the collected groups was determined. Results show that the entomofauna of the Ciudad Universitaria is characterized by low values of diversity, higher values of richness and abundance in the herbaceous strata and by the predominance of groups with phytophagous and polyphagous habits.